Pulmonary Epithelioid Hemangioendothelioma-Mimicking Mesothelioma - Zeynep Bayramoglu; Tolga Semerkant; Hıdır Esme; Yasar Unlu (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
Pulmoner epithelioid hemangioendothelioma is a rare and multifocal malignant tumor of vascular origin. Patients are generally asymptomatic. Chest pain, cough, weight loss, hemoptysis, and pleural effusion are seen in symptomatic patients. Moreover, it is more common in women. It is difficult to diagnose the patients based on clinical and radiological findings. Histopathological examination is the gold standard. We here aimed to present our pulmonary epithelioid hemangioendothelioma patient pre-diagnosed with mesothelioma when she was admitted to the hospital with dyspnea and had bilateral multiple nodules and bilateral pleural effusion.